New directions in macromodelling essays in honor of J. Michael Finger - Welfe, Aleksander (Contributions to economic analysis ;, 2004)
The monograph concentrates on recent developments in modelling economic processes on macro level. Namely there are two main areas of interest: co-integration analysis and the use of high frequency time series. Special emphasis is put on testing, application of VEqCM models to I(1) as well as I(2) variables and structuralization of VAR. Volatility is analysed within traditional and Bayesian approach.